Visual Literacy, Psychological Counseling and Phototherapy: A Model Application - (:unkn) unknown (TURKISH EDUCATION ASSOC, 2015)
Phototherapy is generally described as the use of photography, a visual image, for the communication in the process of therapy/counseling. The purpose of this study is to introduce the phototherapy technique as a method which will increase therapeutic communication in the process of psychological counseling and to present an example for training purposes based on the use of the technique. The study was conducted in the phenomenology design, one of the qualitative research patterns. The study group was comprised of nine senior students who have been in the department of psychological counseling and guidance. The data were collected with the structured interview technique using photography. As a result of the application, it was observed that the use of photography enabledthe initiation and deepening of communication among the group members. In respect to the meaning of the photos chosen, eight members of the study group have brought a photo with a positive meaning and one has brought a photo with a negative meaning. It was inspected that each participant clearly and thoroughly remembered the story of the photo he brought fort he study and expressed that they had the same feeling at the moment. It was found that each member attributed a different meaning and created a different story for the same photo. The findings were discussed in the light of the literature and suggestions were made based on this.
Keywords: Visual literacy; Psychological counseling; Phototherapy; Photography